Working with high-risk youth a relationship-based practice framework - Smyth, Peter (Routledge, Taylor & Francis Group, 2017)
This book focuses on high-risk youth - whose struggles include neglect and abuse, alcohol and drug abuse, the risk of being exploited, mental health issues, and the inability to self-regulate and trust - a population of youth that government child welfare services and community agencies struggle to serve adequately. The focus has traditionally been on punishment-consequence interventions and demanding compliance, but experience and research shows they can be better served through relationship-based practice incorporating harm reduction principles, resiliency and strength-based approaches, community collaboration, and an understanding that these youth typically come from experiences of early trauma impacting their brain development and their ability to form attachments.